Poisson structure and symmetry in the Chern-Simons formulation of (2 + 1)-dimensional gravity - Meusburger, Cathérine; Schroers, Bernd (Classical and Quantum Gravity, 2003)
In the formulation of (2+ 1)-dimensional gravity as a Chern-Simons gauge theory, the phase space is the moduli space of flat Poincaré group connections. Using the combinatorial approach developed by Fock and Rosly, we give an explicit description of the phase space and its Poisson structure for the general case of a genus g oriented surface with punctures representing particles and a boundary playing the role of spatial infinity. We give a physical interpretation and explain how the degrees of freedom associated with each handle and each particle can be decoupled. The symmetry group of the theory combines an action of the mapping class group with asymptotic Poincaré transformations in a nontrivial fashion. We derive the conserved quantities associated with the latter and show that the mapping class group of the surface acts on the phase space via Poisson isomorphisms.